Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai Negeri Sipil pada Kantor Kementerian Agama Kabupaten Pasuruan - Mustainah Mustainah; Pompong Budi Setiadi; Sri Rahayu (Journal on Education, 2023)
The research objective was to determine the effect of leadership style on the performance of civil servants and leadership style: responsibility, inspiration, honesty and integrity, self-confidence, easy communication on employee performance. Respondents were 50 people. Analysis using multiple linear regression. The results of the leader's responsibility do not affect employee performance, partially inspire influence, honesty and integrity influence, confidence influences, and easy to communicate on employee performance. Simultaneously leadership style influences employee performance